Effect of Pulse Current on Serrated Flow of 5086 Al Alloy. Issue 208 (12th June 2020) - Chu, Xingrong; Lin, Shuxia; Ao, Dongwei; Yue, Zhenming; Gao, Jun
Abstract: The effect of pulse current on the serrated flow of 5086 Al alloy was investigated through uniaxial tensile test at room temperature. The serrated yielding phenomenon was observed without pulse current, while the serration morphology was obviously changed and even suppressed by the pulse current. The experimental results shown that pulse current can effectively eliminate serrated yielding effect. One-parameter approach analysis results and microstructure evolution showed that the pulse current can accelerate the occurrence of dynamic recrystallization and the extent of deformation increased with increasing current density.